Drug-instigated hypertension: analysis of risk indicators - Pereira , Arthur Van Lauter Albuquerque (2023)
This study aims to expose the main concepts about drug-induced arterial hypertension and indicate the best management of the disease. And as secondary objectives, demonstrate the drugs that can potentiate the disease and assist health professionals in making better decisions for multidisciplinary treatment. A review of articles was carried out in the databases Medical Literature Analysis and Retrievel System Online (MEDLINE), Scientific Electronic Library Online (SciELO), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), Directory of Open Access Journals ( DOAJ) and PubMed, with the following Health Sciences Descriptors (DeCS): Drugs; Hypertension; Secondary. Selecting articles between the periods of 2002 and 2023, in English, Portuguese, English and Spanish, to increase the level of relevance and quality of the review. Due to these descriptions, 1029 articles were found, and the titles, abstracts and results were analyzed. Therefore, filters were used based on: containing main subjects (HAS management), availability of the broad and complete version, containing keywords, languages: Portuguese, English and Spanish and the period from 2002 to 2023. It is understood that the Hypertension is a key disease for poor therapeutic outcomes and a risk factor for several pathologies. The worldwide prevalence is indelible and the vast mortality rates overshadow medical science. In this context, drug-induced hypertension is yet another problem that requires interventions and studies to avoid future complications, such as an increase in heart disease. Cases where the drug cannot be suspended must be analyzed and alternative and precise goals and therapeutic lines must be outlined. In addition to excluding any contact with drugs of illicit origin or inappropriate substances that affect the body.